Springs Outflows in Diverse Geology and Geomorphology of Seti Khola Watershed, Western Nepal (Journal of Institute of Science and Technology, 2025)
Springs are crucial for supporting life and balancing ecosystems and vary in outflow from place to place. A study was conducted in the mid-hill region of western Nepal, which spans between carbonate (44%) and non-carbonate (56%) lithology. A field survey identified 175 perennial springs, which were categorized based on their outflows using methods such as bucket-stopwatch, weir, and float techniques. Springs were grouped into minimum 0.1-10 liter per minute (lpm), intermediate 10-60 lpm, and maximum outflow 60-300 lpm categories. This study assessed the characteristics of springs, focusing on their lithology, elevation, landforms, and land cover. Springs in carbonate-dominant areas consistently exhibited higher outflows than those in non-carbonate areas. Intermediate outflow was the most frequent, particularly in forested areas. The occurrence of springs is significantly influenced by the underlying geology, fractured networks, conduits, and resulting topography. Soil types, especially eutric cambisols, supported higher outflow in intermediate and maximal, whereas gleyic cambisols had minimal outflows. Springs with intermediate outflows were crucial for local water needs, whereas maximal, although rare, were vital for ecosystem health and larger water supply. These findings underscore the importance of spring conservation and sustainable watershed management in maintaining spring outflow and mitigating water scarcity.